Complete the equation \( \begin{array}{r}9 \frac{1}{3} \quad 8+\frac{3}{3}+\frac{1}{3} \\ -3 \frac{2}{3}-3 \frac{2}{3}\end{array} \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To complete the equation, we first convert the mixed numbers into improper fractions and perform the calculations. The first term, \(9 \frac{1}{3}\), can be converted as follows: \[ 9 \frac{1}{3} = \frac{28}{3} \] Now let's add the second part of the equation: \[ 8 + \frac{3}{3} + \frac{1}{3} = 8 + 1 + \frac{1}{3} = 9 + \frac{1}{3} = \frac{28}{3} + \frac{1}{3} = \frac{29}{3} \] Now we calculate the entire first part: \[ \frac{28}{3} + \frac{29}{3} = \frac{57}{3} \] Next, we compute the second part: Both terms, \( -3 \frac{2}{3} \), convert to: \[ -3 \frac{2}{3} = -\frac{11}{3} \] So, \[ -\frac{11}{3} - \frac{11}{3} = -\frac{22}{3} \] Now we put it all together: \[ \frac{57}{3} - \frac{22}{3} = \frac{57 - 22}{3} = \frac{35}{3} \] Thus, the completed equation results in: \[ \frac{35}{3} \] or \(11 \frac{2}{3}\).